A Preliminary Investigation of Additive Manufacture to Fabricate Human Nail Plate Surrogates for Pharmaceutical Testing - Bruno C. Sil; Avnish Patel; Jonathan M. Crowther; David J. Moore; Jonathan Hadgraft; Stephen T. Hilton; Majella E. Lane (MDPI AG, 2019)
In vitro permeation studies using nail clippings or nail plates are commonly used in the development of transungual formulations. However, there are ethical, safety and cost issues associated with sourcing such tissues. Herein, we describe a preliminary approach is described for the design and manufacture of a human nail model surrogate based on 3D printing. To evaluate these 3D printed constructs, nails were mounted in conventional glass Franz cells and a commercial antifungal lacquer formulation containing ciclopirox olamine was applied daily to the surrogate printed surfaces for a period of 14 days. On days 8 and 14, the surfaces of the 3D printed nails were washed with ethanol to remove excess formulation. Confocal Raman spectroscopy (CRS) was used to profile the drug in the 3D printed nail. At the end of the Franz cell studies, no drug was observed in the receptor phase. CRS studies confirmed penetration of the active into the model nails with reproducible depth profiles. Our ongoing work is focused on synthesising commercial and non-commercial printable resins that can replicate the physical and chemical characteristics of the human nail. This will allow further evaluation of actives for ungual therapy and advance the development of the surrogate nail tissue model.